Representasi Maskulinitas Tokoh Lelaki Dalam Film Susah Sinyal - Jusuf Fadilah; Widarti Widarti; Dina Andriana (Universitas Bina Sarana Informatika, 2021)
Abstract - This scientific research aims to determine the connotation and extension of Iwan, one of the supporting roles in the movie